Clinical response to liposomal doxorubicin and rituximab in HHV-8-associated multicentric Castleman's disease in an HIV-positive patient. Issue 12 (December 2016) - Osa, Morichika; Maeda, Takuya; Misawa, Kazuhisa; Imai, Kazuo; Fujikura, Yuji; Kawana, Akihiko
Abstract: We report a patient with HIV-associated multicentric Castleman's disease who had recurrent human herpesvirus-8 viremia associated with intermittent febrile exanthema and lymphadenopathy. Although the patient relapsed after single-agent treatment with liposomal doxorubicin, weekly infusions of rituximab led to complete remission even though the reactivation of the Kaposi's sarcoma was unfortunately observed. Rituximab could not only eliminate the accumulation of HHV-8 load but also play a part in the modulation of dysregulated CD20-positive B cells in HIV-associated multicentric Castleman's disease.